Amasa Trowbridge papers - Trowbridge, Amasa, 1779-1859.
Three ALsS (1855 November 1 and 1856 April 10 and June 27) written by Trowbridge to Benson J. Lossing relating to Trowbridge's experiences during the War of 1812; accounts of the Battle of York, Toronto, Ont. (1813), the capture of Fort George, Niagara-on-the-Lake, Ont., (1813), and the siege of Fort Erie, Ont. (1814); drawings of Toronto, Fort George, and Fort Erie during the War of 1812; clipping and photocopy of a drawing of fortifications at Pensacola, Fla.; autobiographical sketch (undated); article pertaining to Miles Vernon; and obituary of Edmund Pendleton Gaines.
Surgeon and army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Gaines, Edmund Pendleton, -- 1777-1849.; Lossing, Benson John, -- 1813-1891 -- Correspondence; Vernon, Miles; York, Battle of, Toronto, Ont., 1813.; Fortification -- Florida -- Pensacola; Florida -- History -- War of 1812.; Fort George (Niagara-on-the-Lake, Ont.); Fort Erie (Ont.) -- History -- Siege, 1814.; Ontario -- History -- War of 1812.; United States -- History -- War of 1812 -- Campaigns; United States -- History -- War of 1812 -- Medical care; Army officers; Surgeons